PCR-Based Identification and Epidemiological Assessment of Entamoeba gingivalis Among Patients With Periodontal Disorders - Qahtan Adnan Rasheed Rasheed (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Entamoeba gingivalis is an oral protozoan frequently found in dental plaque and periodontal pockets and has been reconsidered for its role in oral pathology. Specific Background: Recent molecular approaches have enabled improved detection of this organism in patients with gingivitis and periodontitis. Knowledge Gap: Despite growing interest, limited data exist comparing conventional microscopy and polymerase chain reaction (PCR) for accurate detection and subtype identification in clinical samples. Aims: This study aimed to determine the prevalence of E. gingivalis among periodontal disease patients and to compare the diagnostic performance of microscopy and PCR. Results: Among 120 patients, 7.5% tested positive for E. gingivalis, while 92.5% were negative. PCR confirmed all positive isolates and demonstrated higher sensitivity in detecting low-level infections, with all isolates showing strong genetic similarity to the ST1 subtype. Novelty: This study integrates molecular detection and phylogenetic analysis to confirm subtype distribution in a clinical population. Implications: PCR is recommended as a reliable diagnostic tool for accurate detection and epidemiological assessment of E. gingivalis, supporting improved identification in periodontal disease research and clinical practice. Highlights: • Low detection rate of oral protozoan observed in clinical samples• Molecular method identifies subtype clustering within regional isolates• Diagnostic comparison reveals higher sensitivity of amplification-based testing Keywords: Entamoeba Gingivalis, Periodontal Disease, Polymerase Chain Reaction, Molecular Detection, Phylogenetic Analysis